2003
DOI: 10.1023/a:1024568732213
|View full text |Cite
|
Sign up to set email alerts
|

Participation and Satisfaction with Surgical Treatment Decision-Making in Breast Cancer Among Chinese Women

Abstract: Most Chinese women want shared TDM and to know their surgeon's treatment preference. Over-involved women are at greater risk of difficulties and doubts in TDM and under-involved women perceive a lack of time and information to make their decision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
93
6

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(104 citation statements)
references
References 31 publications
5
93
6
Order By: Relevance
“…1,[6][7][8][9][10][11][12][13][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] The patients' expectations also depend on the type of the disease, 15,20 or the type of the malignancy. 13,15,19,25 Most of the literature data on the attitude of breast cancer patients towards being informed, and participation in treatment decision come from Canada, 15,17,18,26,32 the US, 7,10,25,[27][28][29][30][31]34 Australia, 6,9,…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,[6][7][8][9][10][11][12][13][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] The patients' expectations also depend on the type of the disease, 15,20 or the type of the malignancy. 13,15,19,25 Most of the literature data on the attitude of breast cancer patients towards being informed, and participation in treatment decision come from Canada, 15,17,18,26,32 the US, 7,10,25,[27][28][29][30][31]34 Australia, 6,9,…”
Section: Discussionmentioning
confidence: 99%
“…26 Among Chinese women, 59% wanted a shared decision-making for surgery, and 80% succeeded to participate as much as desired; older age predicted a passive role. 24 Maly et al found that active decision-making on the type of breast surgery among women older than 55 years did not depend on age, but was promoted by special solicitation of the patients' preferences. 28 Among American women, higher education was significantly related to the patient's activity.…”
mentioning
confidence: 99%
“…However, research indicates that SDM accounts for only a small amount of variance in some of these outcomes [7], and is not always practical, or desired by patients [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indeed shown that pressuring patients to be more involved than they want in the decision-making process provokes anxiety (Hack, Degner, & Dyck, 1994), lower satisfaction with care and decisional regret (Lantz et al, 2005), and less confidence in having made the correct treatment choice (Lam, Fielding, Chan, Chow, & Ho, 2003). Instead of advocating patient participation as such, a more fruitful approach might be to establish a good match between patients' preferred levels of participation and their actual levels of participation.…”
Section: Matching Patients' Preferred and Actual Levels Of Participationmentioning
confidence: 99%